Kriptografski sistemi - Šalamon, Matej (Uporabna informatika (Ljubljana), 1999)
Computer networks eavesdropping is a very easy task for an everage programmer.It is almost impossible to assure confidentially of information without using criptographic systems. Various concepts of cryptographic systems that are currently used in the computer networks will be briefly presented.
Keywords: kodiranje; kriptografski sistemi; prenos podatkov; računalniške mreže; šifriranje; tajnost